PENINGKATAN KETERAMPILAN MENGKOMUNIKASIKAN DAN PENGUASAAN KONSEP KESETIMBANGAN KIMIA SISWA MELALUI MODEL LEARNING CYCLE 5E - Anna Musmita Sari; Ratu Betta Rudibyani; Tasviri Efkar (Universitas Lampung, 2013)
The aim of this research is to describe the effectiveness of LC 5E learning model in improving communicate skills and mastery of concepts students on the material chemical equilibrium. The population in this study were all students of class XI IPA in State Senior High School 1 Natar academic year 2012-2013. Sampling was done by purposive sampling technique. The sample in this research was first class XI IPA2 as experiment class and class XI IPA3 as control class. This research used quasi-experimental research design with Non Equivalent Control Group Design. Effectiveness is measured LC 5E learning model based n-Gain increased significantly between the control class and the experimental class, with using two different test average. The results showed the average value of n-Gain skills for communicating control and experimental classes respectively 0,54 and 0,74; and the average value of n-Gain mastery of the concept for the control and experimental classes respectively 0,41 and 0,55. This suggest that the LC 5E learning model effective in improving the skills of communicating and mastery concept of chemical equilibrium students on the material.Kata kunci: model pembelajaran LC 5E, keterampilan mengkomunikasikan dan penguasaan konsep